Derivatives of 3-Aminopyrazine-2-carboxamides: Synthesis, Antimicrobial Evaluation, and in Vitro Cytotoxicity - Bouz, Ghada; Semelková, Lucia; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Navrátilová, Lucie; Kubíček, Vladimír; Kuneš, Jiří; Doležal, Martin; Zitko, Jan (Molecules, 2019)
We report the design, synthesis, and in vitro antimicrobial activity of a series of N-substituted 3-aminopyrazine-2-carboxamides with free amino groups in position 3 on the pyrazine ring. Based on various substituents on the carboxamidic moiety, the series is subdivided into benzyl, alkyl, and phenyl derivatives. The three-dimensional structures of the title compounds were predicted using energy minimization and low mode molecular dynamics under AMBER10:EHT forcefield. Compounds were evaluated for antimycobacterial, antibacterial, and antifungal activities in vitro. The most active compound against Mycobacterium tuberculosis H37Rv (Mtb) was 3-amino-N-(2,4-dimethoxyphenyl)pyrazine-2-carboxamide (17, MIC = 12.5 μg/mL, 46 μM). Antimycobacterial activity against Mtb and M. kansasii along with antibacterial activity increased among the alkyl derivatives with increasing the length of carbon side chain. Antibacterial activity was observed for phenyl and alkyl derivatives, but not for benzyl derivatives. Antifungal activity was observed in all structural subtypes, mainly against Trichophyton interdigitale and Candida albicans. The four most active compounds (compounds 10, 16, 17, 20) were evaluated for their in vitro cytotoxicity in HepG2 cancer cell line; only compound 20 was found to exert some level of cytotoxicity. Compounds belonging to the current series were compared to previously published, structurally related compounds in terms of antimicrobial activity to draw structure activity relationships conclusions.
Keywords: Hep G2 Cells; molekulární konformace; Antifungal Agents; buňky Hep G2; mikrobiální testy citlivosti; houby; pyraziny; Pyrazines; lidé; Anti-Bacterial Agents; Molecular Conformation; buněčná smrt; Fungi; Microbial Sensitivity Tests; Bacteria; Cell Death; antibakteriální látky; antifungální látky; Humans